(untitled) (GYMNASIUM, 2017)
The research methods used to reach the goals of this observational study were: the theoretical documentation method, the direct observation, the inquiry concretized in an interview, specific tests and assessments, and the graphical representation method. The testing method aimed to determined certain morphological-functional indices by using certain control tests such as: the heart rate, the Ruffier test, the supraspinal, tricipital, abdominal, and subscapular skin folds, the Body Mas Index. This study was conducted on 9 subjects from the TNT Sports Club, aged between 25 and 56; even though the number of subjects was small, the research emphasized important aspects regarding the positive reactions of the body to a relatively new (for Romania) form of aerobic effort (spinning) in regards to the improvement of the investigated indices.